Techno-economic analysis of ground source heat pump powered by hybrid photovoltaic-wind-diesel systems in a temperate climate region - Kapicioglu, Abdullah; Kale, Cihangir (Springer, 2023)
As in many European countries, Turkey's foreign energy dependency is quite high. Reducing foreign dependency on energy on a national basis is possible by developing efficient systems and increasing the use of renewable energy systems. This study is created with the idea of combining these two principles. Ground source heat pump systems are widely used for cooling and heating residences due to their higher energy efficiency than ordinary air conditioners. On the other hand, it is possible to support these systems with other renewable energy sources. However, the cost is the most crucial factor for the end user. In this study, a techno-economic analysis of the support of the ground source heat pump system with off-grid hybrid (photovoltaic-wind-diesel) systems, in which renewable energy is included, was carried out. The energy consumption values of the ground source heat pump were simulated annually with the help of the eQUEST program. They were determined as 1988.1 kWh and 1715.9 kWh for heating and cooling, respectively. Seven different power systems were created and optimized using the hybrid optimization model for electric renewable software to meet the electrical energy consumption values obtained. The study results show that the optimum power system to meet the electricity consumption of the designed ground source heat pump is a hybrid system consisting of a 6.9 kW of PV, 4.5 kW of diesel generator, and 10 kWh of battery. In this configuration, the renewable fraction is 84%, and there is no unmet load. For the optimum power system, the levelized cost of electricity and levelized cost of heat values are 0.20 $ kWh(-1) and 0.12 $ kWh(-1), respectively. The results show that hybrid renewable energy-supported power generation systems are cost-effective for ground source heat pumps in remote areas.
Keywords: Ground source heat pump; Hybrid system; Techno-economic analysis; HOMER